Effect of Obesity on the Acute Inflammatory Response in Pregnant and Cycling Female Rats. (12th April 2013) - Pohl, J.; Luheshi, G. N.; Woodside, B.
<x xml:space="preserve">Abstract</x> Nonpregnant female rats have a lower inflammatory response to lipopolysaccharide (LPS) than males and, at late stages of gestation, the fever response to this immunogen is almost completely suppressed. We have shown in males that obesity exacerbates sickness responses to pathogenic stimuli. In the present study, we investigated whether obesity would have a similar effect in females and reverse some of the suppressive effects of pregnancy on the innate immune response. Lean and diet‐induced obese adult Wistar rats were randomly separated into either cycling or mated groups. On day 18 of pregnancy or in the metestrous/dioestrous phase in cycling rats, a single injection of LPS (100 μg/kg) was administered and rats were sacrificed 8 h or 24 h later. In pregnant females, LPS induced a higher increase in body temperature in obese rats only at the 24‐h time point and lower hypothalamic interleukin (IL)‐1β expression and higher circulating levels of IL‐1 receptor antagonist (ra) than their cycling counterparts. Conversely, there was no suppression of inflammatory signals in the white adipose tissue of pregnant rats. At 24 h post LPS, the cell surface marker CD11c and IL‐6 mRNA expression were increased in white adipose tissue from obese rats regardless of reproductive state, whereas IL‐1ra was highest in the LPS‐treated obese pregnant group. In cycling females, LPS induced a higher fever response in obese rats accompanied by higher circulating levels of IL‐6 and IL‐1ra, as well as an increase in circulating leptin only in the obese cycling group. In the hypothalamus, obese rats showed significantly higher expression of nuclear factor‐IL‐6 in at the 8‐h time point. Collectively, these results show that diet‐induced obesity in females is associated with a similar pattern of response to that previously observed in males. On the other hand, obesity had limited effects in pregnant rats, with the exception of white adipose tissue.